(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
CHCV is one of the most significant diseases. According to WHO, 3% of the world’s population is infected with the hepatitis C virus. 3-4 million are registered worldwide. new cases of infection. ChVHC disease reduces ability to work, increases the risk of developing serious complications, increases the cost of medical resources, and increases mortality. There is a high risk of developing liver cirrhosis and hepatocellular carcinomas. Statistics show that more than 360 thousand people die from complications of chronic hepatitis C in the world every year.